The Influence of Financial Performance on Company Value: A Study of Food and Beverage Companies on the IDX in 2020-2023 - Anita Juwita (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Corporate objectives encompass various dimensions, including social responsibility, corporate governance, and human resource development. Effective corporate governance mechanisms enhance a company's image and provide strategic direction aligned with organizational goals. This study employs a causal research method to examine the influence of capital structure, profitability, and leverage on firm value. The firm value is measured using the Price to Book Value (PBV) indicator, while the independent variables include the Debt to Equity Ratio (DER) for capital structure, Return on Equity (ROE) for profitability, and Time Interest Earned (TIE) for leverage. Data for this research was collected using a survey method with a quantitative approach, relying on secondary data from financial statements of companies listed on the Indonesia Stock Exchange. Multiple linear regression analysis was employed to assess the simultaneous effects of independent variables on firm value. Hypothesis testing was conducted using t-tests for individual variables and F-tests for collective impacts, with the coefficient of determination (R2) indicating the extent of explained variance. The results reveal that DER, ROE, and TIE significantly influence firm value. DER negatively impacts firm value, suggesting that companies should manage debt levels effectively to enhance PBV. ROE positively affects firm value by reflecting management efficiency and profitability, encouraging investor confidence and higher valuations. However, excessive leverage can undermine financial stability despite its potential to increase shareholder returns. Therefore, companies should maintain an optimal capital structure, balancing profitability and financial risk to maximize firm value.